Association between necropsy evidence of disseminated intravascular coagulation and coagulation variables before death in patients in intensive care units. Issue 2 (February 1988) - Wilde, J T; Roberts, K M; Greaves, M; Preston, F E
Abstract : The necropsy findings in 21 patients on an intensive care unit, on whom coagulation studies had been performed immediately before death, were assessed. Eleven of the patients were retrospectively studied and 10 were reviewed consecutively in a prospective study. Fifteen patients (eight retrospective and seven prospective) had evidence of disseminated intravascular coagulation. Microthrombi were most often found in the lungs and kidneys. The most common abnormal coagulation tests in patients with necropsy evidence of disseminated intravascular coagulation were raised serum concentrations of fibrinogen and fibrin degradation products, prolonged prothrombin time, and reduced platelet counts. Reduced fibrinogen concentrations and a prolonged thrombin time were the least commonly observed abnormalities. There was no difference in either the prevalence or magnitude of abnormality of any particular coagulation variable test result between those patients with evidence of disseminated intravascular coagulation at necropsy and those without.